Bagian Waris Ibu Dalam Gharâiwayn; Analisis Ijtihad Umar dan Ibn Abbas dalam Bagian Waris Ibu - Syuhada' Syuhada' (INSTITUT AGAMA ISLAM BANI FATTAH (IAIBAFA), 2014)
The hint Al-Qur’an on inheritance was so raw and tawqîfiyat though still very limited, and a global cues. Appointment to the rules in the global situation of open space to perform ijtihâd. In the case of the mother’s time with the father and one of the spouses has never happened at the time of the Prophet 'Umar Ibn Khat?t?âb as the caliph should be a decision to give an answer to the solution. By calculation, according to Ibn 'Abbâs in the case gharâiwayn which gives the mother a third of all the treasures, also not out of the possible, that at least one and at most two for each of the mothers and fathers as men and women when it is understood that the scale of the two appeal of the scale maximum and minimum. Display Al-Qur’an that filial to parents with different circumstances is a must give way to the possibility of applying the result of two principal parts. Part of the principal can be attributed to the remaining one-third or one-third of all real estate omission with regard to conditions suitable for the elderly.